Country of first birth and neonatal outcomes in migrant and Norwegian-born parous women in Norway: a population-based study - Eline S. Vik; Roy M. Nilsen; Vigdis Aasheim; Rhonda Small; Dag Moster; Erica Schytt (BMC, 2020)
Abstract Background This study compares subsequent birth outcomes in migrant women who had already had a child before arriving in Norway with those in migrant women whose first birth occurred in Norway. The aim of this study was to investigate the associations between country of first birth and adverse neonatal outcomes (very preterm birth, moderately preterm birth, post-term birth, small for gestational age, large for gestational age, low Apgar score, stillbirth and neonatal death) in parous migrant and Norwegian-born women. Methods National population-based study including second and subsequent singleton births in Norway from 1990 to 2016. Data were retrieved from the Medical Birth Registry of Norway and Statistics Norway. Neonatal outcomes were compared between births to: 1) migrant women with a first birth before immigration to Norway (n = 30,062) versus those with a first birth after immigration (n = 66,006), and 2) Norwegian-born women with a first birth outside Norway (n = 6205) versus those with a first birth in Norway (n = 514,799). Associations were estimated as crude and adjusted odds ratios (aORs) with 95% confidence intervals (CIs) using multiple logistic regression. Results Migrant women with a first birth before immigrating to Norway had increased odds of adverse outcomes in subsequent births relative to those with a first birth after immigration: very preterm birth (22-31 gestational weeks; aOR = 1.27; CI 1.09-1.48), moderately preterm birth (32-36 gestational weeks; aOR = 1.10; CI 1.02-1.18), post-term birth (≥42 gestational weeks; aOR = 1.19; CI 1.11-1.27), low Apgar score (< 7 at 5 min; aOR = 1.27; CI 1.16-1.39) and stillbirth (aOR = 1.29; CI 1.05-1.58). Similar results were found in the sample of births to Norwegian-born women. Conclusions The increased odds of adverse neonatal outcomes for migrant and Norwegian-born women who had their first births outside Norway should serve as a reminder of the importance of taking a careful obstetric history in these parous women to ensure appropriate care for their subsequent pregnancies and births in Norway.